Autism in the Emergency Department. (October 2014) - Cohen-Silver, Justine Heather; Muskat, Barbara; Ratnapalan, Savithiri
Background . This is a retrospective chart review of autistic patients presenting to the emergency department (ED) in a tertiary care pediatric center during the year 2011. Results . There were 160 ED visits by 130 patients, 25% of visits were repeated, and 20% were admitted to the hospital. There were 126 (79%) male and 34 (21%) female patients mean age of 12 years, 79% had comorbid health conditions. Forty percent were CTAS 2 (Canadian Triage Acuity Score) acuity, 42% of visits were CTAS 3 acuity, and 7% rated their pain as "severe." Visits were for behavior (10%), neurological concern (13%), 3% dental related, and the remainder were for gastrointestinal infections and other complaints. Average length of stay was 6 hours 21 minutes, with 2-hour wait to start assessment with physician. Conclusions . Autism is a prevalent diagnosis and patients with autism are accessing the ED. We hope to use these demographic findings to better serve these patients and their families.